Inovasi Pendampingan Guru PAUD: Upaya Nyata Meningkatkan Kualitas Mengajar di Himpaudi Panceng Gresik - Akhmad Syah Roni Amanullah; Fithrotin; Zaskia Salsabilla Rachma (LP3M IAIFA Kediri, 2026)
This community service initiative aims to improve the teaching quality of Early Childhood Education (PAUD) teachers who are members of the Indonesian Association of Early Childhood Educators and Support Staff (Himpaudi) in Panceng Sub-district, Gresik Regency. The activity was held on 31 March 2026 at the Dharma Wanita ECE Mosque, Siwalan, from 08:00 to 13:00 WIB. The method used was participatory mentoring through interactive lectures, group discussions, and simulations. The mentoring materials covered the introduction of teacher identity, the characteristics of a good teacher and the ideal teacher for children, indicators of a high-quality teacher, and an understanding of aspects of child growth and development. The results of the activity showed a significant increase in participants’ understanding, with an average post-test score of 85.6 compared to a pre-test score of 65.2. This mentoring was effective in reflecting upon and strengthening the pedagogical competencies of early childhood education teachers in the local area. Keywords: early childhood education teacher mentoring, teaching quality, Himpaudi, child development.